TREATMENT OF PATIENTS WITH ACUTE DESTRUCTIVE PANCREATITIS USING EXTRACORPOREAL DETOXIFICATION METHODS - Nazarov, D.T.; Klimov, A.E.; Persov, M.Yu.; Andreev, S.S.; Mamedov, S.Kh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
assessment of the effectiveness of extracorporeal detoxification methods in the treatment of patients with severe acute destructive pancreatitis. Material and methods: the study included 84 patients with destructive pancreatitis who were treated at the clinic of faculty surgery of the Peoples’ Friendship University of Russia at the base of the city clinical hospital named after V.V. Vinogradova (Moscow), aged 18 to 80 years. Men 66 (78.6%), women 18 (21.4%). Results: 29 patients died, the overall mortality rate was 34.5%. Among the patients of the 1st group who underwent extracorporeal treatment methods, due to PON with the addition of pneumonia, sepsis, arrosive bleeding, retroperitoneal phlegmon died 12 (24%), the treatment duration was 35 ± 4 days. In the 2nd group, due to PON with the addition of pneumonia, sepsis, arrosive bleeding, retroperitoneal phlegmon, abscess of the omental bursa, pancreatogenic shock, the lethal outcome occurred in 17 (50%), the duration of treatment was 19 ± 1.5 days. Conclusions: earlier the use of extracorporeal detoxification methods for destructive pancreatitis leads to a decrease in mortality of patients in hospital. Extracorporeal detoxification methods for destructive pancreatitis can be used in operated and non-operated patients.